Examining the Effects of Local Government Participation in Economic Development Planning of Sabon-Gari Local Government Area in Kaduna State - Lawal, Yusuf Birisan; Shehu , Lukman Omomeji; Ajao, Yusuf Ibrahim (Kashere Journal of Politics and International Relations, 2025)
Development strategies, efforts and programmes are more and more being designed to induce local participation towards ensuring economic development. It is on this basis that the study examined the relationship between local government participation and economic development planning in Sabon-Gari Local Government. The study adopted qualitative research design relying solely on Face-to-Face interview to generate data for the study with the population comprised of six (6) respondents comprising Local Government Chairman, Vice Chairman, LEEDs Coordinator, Sabon-Gari and Desk Officers (I, II & III). The information from interview section was corroborated by secondary data from relevant documents. Some of the relevant documents reviewed include NEEDs Document, (2005) and LEEDs Implementation Manual, 2005. The data generated from the interviewees were thematically analysed. From the presentation and analysis of data, the study concluded that Local Government participation in NEEDs through LEEDs has promoted economic empowerment and development through a more articulate, forward looking, progressive and radical strategy with its inclusive participatory nature (involving government, private sector and the people) in managing the resources of the country for the benefit of the teeming population. However, many factors have stood against the dreams of this strategy including weak leadership at the centre, debt burden etc. The study therefore, recommended among others the need for Nigeria as a nation through its government should fight for debt relief and the need for a monitoring agency to be established that would help in the service delivery of the NEEDs, SEEDs and LEEDs programmes.